Food behaviors and youth obesity in Pakistan - doi: 10.4025/actascihealthsci.v35i2.11885 - Anjum Hashmi; Jamil Ahmed Soomro; Khalid Saleem (Acta Scientiarum. Health Sciences, 2013)
The epidemic of obesity took off from about 1980 and in almost all countries has been rising inexorably ever since. Only in 1997 did world health organization accept that this was a major public health problem. It is also becoming an important public health problem among Pakistani children due to changes in life style and other factors. The increasing prevalence of childhood obesity and its concomitant health risks justify widespread efforts toward prevention. A Cross-sectional study was conducted to elaborate the various types of foods and change in eating behavior leading to abnormal weight gain among the youth. A total of 504 male and female students of class six to ten were selected through simple random sampling. Anthropometric measurements were done with calibrated instruments using the age and sex specific BMI cut off points according to World Health Organization growth reference. Results showed significant proportion of girls (86%) and boys (85%) had abnormal waist to hip ratio. The determinants of the obesity lie within the rapid changes in food intake behavior and lifestyle patterns which had a clear and significant impact on the prevalence of obesity in youth of Pakistan.